1998
DOI: 10.1016/s0169-5150(97)00032-7
|View full text |Cite
|
Sign up to set email alerts
|

Investigating improved pasture productivity change on the New South Wales tablelands

Abstract: The productivity of improved pastures in Australia's southeastern grazing regions is now bclievcd to be in a sture of long-terni decline. As yer, therc is little economie evidence to support this perception. The analysis reported in this paper secks to examine improved pasture Productivity change l'rom an economie standpoint in a major Australian grazing area, The analysis rests on the central proposition that the productivity of the livestock enterprises is a direct rcflection of pasture productivity. Using b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2000
2000
2013
2013

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…The analysis of these and other data (Vere 1998;D. R. Kemp and D. T. Vere unpublished data) showed that on average, newly sown pastures were carrying 12-14 dry sheep equivalents (dse)/ha in the year sown, particularly from 1970 on.…”
Section: Introductionmentioning
confidence: 94%
“…The analysis of these and other data (Vere 1998;D. R. Kemp and D. T. Vere unpublished data) showed that on average, newly sown pastures were carrying 12-14 dry sheep equivalents (dse)/ha in the year sown, particularly from 1970 on.…”
Section: Introductionmentioning
confidence: 94%
“…This divergence, which resulted in a reduction in soil fertility on sown areas, has been suggested as one of the key reasons for the decline in productivity of legumes in pastures (Vere 1998). In turn, this has influenced livestock production and the productivity and persistence of sown and fertility-responsive grass species (Kemp and King 2001).…”
Section: Introductionmentioning
confidence: 99%